Determination of long-term volume change in lakes by integration of UAV and satellite data: the case of Lake Burdur in Turkiye - Kaya, Yunus; Sanli, Fusun Balik; Abdikan, Saygin (SPRINGER HEIDELBERG, 2023)
Monitoring the water levels and volume changes of lakes and reservoirs enables us to understand the importance of better protection and managing water resources in an ecologically optimum manner. Although some lakes, such as Burdur Lake, are not a source of drinking water, they are home to many endangered animals, endemic plants, and some species. Therefore, monitoring the changes in these lakes over time is important for various reasons. While water level measurement stations in lakes and wetlands provide important information, it may not always be possible to obtain this data. In this study, we investigated the long-term changes in Burdur Lake, a Ramsar site, by integrating the Digital Elevation Model (DEM) obtained by the unmanned aerial vehicle (UAV) with shoreline information obtained from the Landsat mission. This study aimed to investigate the usability, advantages, and disadvantages of the UAV-Landsat integration for volume calculation. As a result, we successfully determined the water level as r= 0.999 and the cumulative volume loss at a rate of 97.5%. Burdur Lake experienced a significant reduction in its area decreasing from 206 to 120 km2 (42%) between 1984 and 2022. Furthermore, the water volume of the lake decreased by 2.70 km3 over a span of 38 years. This study demonstrates the potential and limitations of the presented UAV-remote sensing integration. Our proposed method is beneficial for determining short and long-term water levels and volumetric changes with high accuracy.
Keywords: UAV; Landsat; Volume calculation; Water surface level; Ramsar site; STRUCTURE-FROM-MOTION; AERIAL VEHICLE UAV; WATER-LEVEL; LANDSAT 8; LOW-COST; EXTRACTION; INDEX; PHOTOGRAMMETRY; ALTIMETRY; RIVERS; Environmental Sciences & Ecology